English Education Teaching Practice Program: Classroom Interaction and Classroom Language Analysis - Nuroida Ainun Azizah; Christianti Tri Hapsari (Linguistic, English Education and Art (LEEA) Journal, 2026)
This paper aimed to fill this gap by analyzing the forms of interaction during classroom learning among English Education students while they were conducting teaching practice in junior high schools for a period of two months. The researchers used a quantitative descriptive approach to analyze seven teaching videos ranging from fifty minutes to one hour in length using Flanders Interaction Analysis Categories (FIAC, 1970) and Salaberri's (1995) eight classroom language categories. Data were coded using Microsoft Excel and were analyzed using SPSS to find the frequency, mean, and proportion of occurrence. The key findings show that interactions were dominated by teacher-dominated or direct influence, with an average of (68.83%, SD=13.61) and indirect influence, with an average of (31.17%), with only one video focusing on student-centred interaction (I/D ratio=1.11%). Between Salaberri's (1995) categories, the spontaneous situation category was dominant (48.78%), followed by social interaction (18.36%) and basic instruction (13.09%), whereas error handling was not found at all or was non-existent (0%). These findings indicate that prospective teachers are overly reliant on direct instructional use of language, which limits opportunities for communication. The conclusions of this study can be used to inform teacher training programs to improve indirect influence strategies and error correction skills for a more effective EFL classroom interaction. Keywords: Classroom Language, Classroom Interaction, EFL Indonesia, Teaching Practice, Preservice Teachers